2018
DOI: 10.1155/2018/7196873
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Optimum Mixture Ratio of Reactive Powder Concrete

Abstract: To optimize the main components of reactive powder concrete (RPC) for various curing methods, based on the fluidity and compressive strength, an inclusive experimental research is conducted on 58 different mixture ratios. e results indicate that owing to the increase of the cement strength, the RPC fluidity decreases and the cement strength is not proportional to the compressive strength. e addition of the fly ash and the nano-microbead is an effective way to improve the fluidity, and it is required at the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It was concluded that the treatment method affects the strength considerably; autoclave curing showed better performance compared to the stream curing regimen, especially for the mixtures that contained lower cement. Mingyang and Wenzhong [20] cast 58 RPC mixtures with different mixture proportions and examined the effect on compressive strength. They found the use of fly ash and nano-silica enhanced the compressive strength, and the percentage of silica foam ranges from 0.15% to 0.3%.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the treatment method affects the strength considerably; autoclave curing showed better performance compared to the stream curing regimen, especially for the mixtures that contained lower cement. Mingyang and Wenzhong [20] cast 58 RPC mixtures with different mixture proportions and examined the effect on compressive strength. They found the use of fly ash and nano-silica enhanced the compressive strength, and the percentage of silica foam ranges from 0.15% to 0.3%.…”
Section: Introductionmentioning
confidence: 99%
“…It removes coarse aggregate on the basis of ordinary concrete, and optimizes the compactness of aggregate with quartz sand, improving the homogeneity of matrix, and reducing porosity by adding active mineral admixtures such as silica fume and fly ash, while improving the microstructure by thermal curing [1][2][3]. In order to achieve ultrahigh strength of RPC, current research uses quartz sand [4][5][6] to prepare RPC through heat curing [7] or autoclave curing [8,9]. Thermal and autoclave curing can effectively improve RPC mechanical properties and promote its hydration process of RPC and enhance pozzolanic activity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This procedure produces cement-based materials of high strength, high durability, high toughness, and good volume stability [1,2,3]. Existing studies have used quartz sand [4,5,6] and river sand [7,8,9] to prepare RPC. However, quartz sand increases preparation costs, and the massive utilization of river sand causes shortages in resources.…”
Section: Introductionmentioning
confidence: 99%